2010
DOI: 10.1371/journal.pgen.1000985
|View full text |Cite
|
Sign up to set email alerts
|

Mice with Alopecia, Osteoporosis, and Systemic Amyloidosis Due to Mutation in Zdhhc13, a Gene Coding for Palmitoyl Acyltransferase

Abstract: Protein palmitoylation has emerged as an important mechanism for regulating protein trafficking, stability, and protein–protein interactions; however, its relevance to disease processes is not clear. Using a genome-wide, phenotype driven N-ethyl-N-nitrosourea–mediated mutagenesis screen, we identified mice with failure to thrive, shortened life span, skin and hair abnormalities including alopecia, severe osteoporosis, and systemic amyloidosis (both AA and AL amyloids depositions). Whole-genome homozygosity map… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 39 publications
(56 reference statements)
2
67
1
Order By: Relevance
“…It should be noted that all three proteins are fully acylated in the presence of WT Swf1, and no acylation is detectable for swf1⌬ strains. develop neuropathological and behavioral features of Huntington disease (41), and mice with a nonsense mutation in this gene present with alopecia, osteoporosis, and systemic amyloidosis (42). Most other PATs with the divergent DHHC motif that we identified have not yet been studied.…”
Section: Discussionmentioning
confidence: 94%
“…It should be noted that all three proteins are fully acylated in the presence of WT Swf1, and no acylation is detectable for swf1⌬ strains. develop neuropathological and behavioral features of Huntington disease (41), and mice with a nonsense mutation in this gene present with alopecia, osteoporosis, and systemic amyloidosis (42). Most other PATs with the divergent DHHC motif that we identified have not yet been studied.…”
Section: Discussionmentioning
confidence: 94%
“…While DHHC17/HIP14 has a number of substrates for palmitoylation, the specific substrates of DHHC13/HIP14L are still limited. DHHC13/HIP14L was only reported to palmitoylate GAD65 [76] , huntingtin [76,229], and SNAP-25 [230]. It was recently reported that the DHHC13/HIP14L-deficient hip14l _ / _ mice exhibited the HD-like progressive neuropathological deficits, including progressive loss of striatal and cortical volume and motor impairment [230].…”
Section: Huntingtin and Palmitoylationmentioning
confidence: 99%
“…We previously reported that Zdhhc13 skc4 mice (MGI: 2671845) generated through N-ethyl-N-nitrosourea (ENU) mutagenesis exhibited alopecia, hyperkeratosis, amyloidosis, and osteoporosis (Saleem et al, 2010). We also reported that Zdhhc13, a novel regulator, regulates postnatal skeletal development and bone mass acquisition via Palmitoylation of MT1-MMP, thus revealing the role of Palmitoylation in the pathogenesis of human osteoporosis (Song et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The observation of alopecia and hyperkeratosis in mice with a deficiency in DHHC13, a palmitoyl-acyl transferase (Saleem et al, 2010), prompted us to explore the role of palmitoylation in the skin and hair differentiation.…”
Section: Introductionmentioning
confidence: 99%